2020
DOI: 10.1093/infdis/jiz694
|View full text |Cite
|
Sign up to set email alerts
|

Viral Hepatitis and Human Immunodeficiency Virus Testing and Linkage to Care for Individuals Enrolled in an Opioid Treatment Program

Abstract: Background In the United States, many opioid treatment programs (OTPs) do not offer viral hepatitis (VH) or human immunodeficiency virus (HIV) testing despite high prevalence among OTP clients. We initiated an opt-out VH and HIV testing and linkage-to-care program within our OTP. Methods All OTP intakes are screened for VH and HIV and evaluated for rescreening annually. A patient navigator reviews laboratory results and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As seen in SUD A’s experience, the retirement of the initial champion and the hiring of a replacement staff impacted the testing rates as well as the follow-up of treatment referrals and outcomes. Rowan et al implemented a patient navigator role to review all laboratory results and provide support for linkage or relinkage to care at a MOUD clinic with improvements in testing and treatment of HCV (Rowan et al, 2020). This role in SUD A also resulted in successful relinkage to HIV and referrals for HCV care and this may be particularly relevant for sites that do not provide on-site HCV treatment (Butner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in SUD A’s experience, the retirement of the initial champion and the hiring of a replacement staff impacted the testing rates as well as the follow-up of treatment referrals and outcomes. Rowan et al implemented a patient navigator role to review all laboratory results and provide support for linkage or relinkage to care at a MOUD clinic with improvements in testing and treatment of HCV (Rowan et al, 2020). This role in SUD A also resulted in successful relinkage to HIV and referrals for HCV care and this may be particularly relevant for sites that do not provide on-site HCV treatment (Butner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…13,16 Many studies have shown that targeted HCV screening at opioid treatment programs, drug detoxification centers, and halfway houses increases HCV diagnosis rates, and colocalizing HCV treatment at these locations increases HCV treatment uptake and completion. 33,38,39 Prisons have instituted opt-out HCV testing at intake. [40][41][42] Another option is POC testing at mobile clinics, shelters, and street medicine providers.…”
Section: Barriers In the Quest To Eliminate Hcvmentioning
confidence: 99%
“…Recent studies have highlighted the efficacy of hepatitis C screening in these settings. [17][18][19][20][21][22][23] Socioeconomic barriers prevalent in the OUD population often contribute to poor treatment adherence. Successful linkage to care strategies that use tools to overcome these barriers is imperative for good patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Given this lack of engagement with primary care, it is imperative that HCV screening efforts and subsequent referral for treatment be maximized in venues such as emergency departments, medication-assisted therapy (MAT) clinics, homeless shelters, needle exchange programs, prison clinics, federally qualified health centers, and acute care hospitals. Recent studies have highlighted the efficacy of hepatitis C screening in these settings 17–23 . Socioeconomic barriers prevalent in the OUD population often contribute to poor treatment adherence.…”
Section: Introductionmentioning
confidence: 99%